Empowering Educators: Assessing Climate Change Awareness among Secondary School Teachers in Ogun State, Nigeria, to Enhance Environmental Stewardship - Kareem, Musiliu Iyanda; Olatunji, Rotimi Williams (Journal of Sustainability and Environmental Management, 2024)
Climate change is a pressing global issue, and teachers play a crucial role in developing environmental awareness and stewardship among students. This study aimed to assess the climate change knowledge and information sources of secondary school teachers, as well as any potential differences in their awareness levels based on gender and school location (urban vs. rural) in Ado-Odo/Ota Local Government of Ogun State. A survey design was employed for this study. A total of 150 teachers were sampled from 20 secondary schools using a stratified sampling technique, out of a population of 450 teachers. Data was collected using a 17-item questionnaire structured on a 4-point Likert scale. The instrument was validated by experts and found to be reliable with a coefficient of 0.85 using the product-moment correlation coefficient. Three research questions and four hypotheses were formulated and tested using both descriptive and inferential statistical tools, including the one-sample chi-square test for goodness of fit and the Mann-Whitney U test. The findings showed that the teachers in the areas of study have substantial knowledge about climate change, but the information sources are significantly low. The results also indicated that there is no statistically significant difference in the level of climate change awareness between the male teachers and female teachers. The study revealed that the differences between educators in urban and rural areas are not statistically significant. As established by our findings, it was concluded that teachers having insufficient information sources on climate change will impact the enhancement of environmental stewardship. It is hereby recommended that policymakers and educational authorities provide educators with more comprehensive and accessible information on climate change.